PENGARUH MOLTING TERHADAP STRUKTUR DAN PERKEMBANGAN CANGKANG PADA LOBSTER HIJAU PASIR (Panulirus homarus L., 1758) - T Trijoko; Heri Aji Nurcholis (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2018)
Lobster merupakan komoditas laut yang memiliki nilai jual tinggi dan selalu mengalami kenaikan, khususnya pada lobster hijau pasir (Panulirus homarus L., 1758). Agar pemanfaatan sumberdaya lobster di perairan ini tetap lestari maka perlu dilakukan pengelolaan yang rasional dengan mempertimbangkan masukan dari aspek biologi. Penelitian ini bertujuan untuk menganalisis pengaruh molting terhadap struktur dan perkembangan cangkang pada lobster hijau (Panulirus homarus L., 1758). Sampel yang digunakan berupa 35 lobster yang terdiri dari ukuran 50 gram hingga 250 gram, yang dipelihara di Unit Kerja Budidaya Air Laut Sundak, Yogyakarta. Analisa data yang dilakukan adalah dengan menggunakan prinsip dasar perbandingan data deskriptif, dimana digunakan perbandingan data dengan cangkang lobster sebelum molting (proecdysis), sesaat molting (ecdysis), dan sesudah molting (postecdysis). Hasil menunjukkan bahwa struktur cangkang pada lobster proecdysis memiliki struktur yang lengkap dan ketebalan cangkang yang paling tinggi. Unsur penyusun cangkang seperti C, O, N, dan Ca paling banyak ditemukan di dalam cangkang. Selain itu, cangkang lobster memiliki rasio berat yang lebih tinggi dibandingkan dengan daging lobster. Cangkang lobster postecdysis memiliki rasio berat cangkang tertinggi, sedangkan pada lobster ecdysis memiliki rasio berat daging yang paling tinggi.Kata Kunci: Struktur, Perkembangan, Cangkang, Lobster, Panulirus homarusABSTRACTLobster is a marine commodity that has a high selling value and always increases, especially in the Scalloped Spiny Lobsters (Panulirus homarus L., 1758). In order for the lobster resources in these waters remains sustainable it is necessary to do a rational management by considering the biological aspects. This study aims to analyze the effect of molting on to shell structure and development on Scalloped Spiny Lobsters (Panulirus homarus L., 1758). The sample used was 35 lobsters consisting of sizes 50 grams to 250 grams, which were kept in the Sundak Sea Water Farming Unit, Yogyakarta. Data analysis is done by using the basic principle of descriptive data comparison, where used comparison of data with lobster on proecdysis (before molting), ecdysis (on molting), and postecdysis (after molting). The results show that the shell structure of the lobster on proecdysis has the complete structure and the highest shell thickness. Shell constituent elements such as C, O, N, and Ca are found mostly in the shell. In addition, lobster shells have a higher weight ratio compared to lobster meat. The lobster shells on postecdysis has the highest shell weight ratio, whereas on the ecdysis lobster has the highest meat weight ratio.Key word: Structure, Development, Shell, Lobster, Panulirus homarus ABSTRACTLobster is a marine commodity that has a high selling value and always increases, especially in the Scalloped Spiny Lobsters (Panulirus homarus L., 1758). In order for the lobster resources in these waters remains sustainable it is necessary to do a rational management by considering the biological aspects. This study aims to analyze the effect of molting on to shell structure and development on Scalloped Spiny Lobsters (Panulirus homarus L., 1758). The sample used was 35 lobsters consisting of sizes 50 grams to 250 grams, which were kept in the Sundak Sea Water Farming Unit, Yogyakarta. Data analysis is done by using the basic principle of descriptive data comparison, where used comparison of data with lobster on proecdysis (before molting), ecdysis (on molting), and postecdysis (after molting). The results show that the shell structure of the lobster on proecdysis has the complete structure and the highest shell thickness. Shell constituent elements such as C, O, N, and Ca are found mostly in the shell. In addition, lobster shells have a higher weight ratio compared to lobster meat. The lobster shells on postecdysis has the highest shell weight ratio, whereas on the ecdysis lobster has the highest meat weight ratio.Key word: Structure, Development, Shell, Lobster, Panulirus homarus